Letr@mento no universo fanfiction : do impresso à tela - Alves, Waldinéia Lemes da Cruz (2015)
This thesis aims to investigate and analyze the movements of reading and writing of fanfiction in the virtual community Nyah! Fanfiction. This website has fictional stories produced by amateur writers and, therefore, it is reference to the most avid fan fiction readers in Brazil. The study is theoretically supported by Soares (2010), Kleiman (1995) Lankshear and Knobel (2006), Lévy (1999), Rojo (2009, 2012, 2013), Shepherd (2013), Correa (2007), Coscarelli (2011), Pinheiro (2013), Vargas (2005), Freitas and Costa (2006) and other. The research was guided by a question that led to the data analysis: 1) How reading and writing of fictional stories can become literacy practices in Nyah! Fanfiction? The research methodology has a qualitative and interpretative approach supported by Flick (2009) and Bortoni-Ricardo (2008), based on the non-participant observation method that guided the generation of the data. The outcomes have pointed out to an appreciation of creation and authorship of fanfiction readers and writers in a virtual territory that favors an asynchronous interaction and fictional texts that encourage social practices that are constituted by the written language and therefore for being available on the web, this way they provide and expand social relationships beyond traditional agencies and creat spaces for collective and collaborative language learning. Finally, I concluded that the space Nyah! Fanfiction is a literacy environment, because it leads the contemporary individual to participate in real social and interactional events of reading and writing in an active and dynamic way to the digital environment.